The ECB''s unconventional monetary policy and the role of exchange rate regimes in cross-country spillovers - Jakob Roager Jensen; Jakob Guldbæk Mikkelsen; Morten Spange (Danmarks Nationalbank, 2017)
We study the impact of the ECB's large scale asset purchase programme on selected euro area and neighbouring countries. The effects of the programme are assessed by conducting an event study as well as by estimating a structural VAR model using a shadow short rate as a measure of the monetary policy stance. We find that the programme has contributed to reducing longerterm bond yields in the euro area as well as in neighbouring countries. As a consequence of the fixed exchange rate regime, Danish sovereign bond yields have been tracking those of Germany very closely. Countries with a floating exchange rate have experienced an appreciation in response to the asset purchases. The effect on the Danish krone has been neutralised by central bank intervention in the foreign exchange market. A counterfactual exercise shows that the ECB's unconventional monetary policy in the beginning of 2015 reduced the term spread in Denmark by at least 50 basis points. – – Vi undersøger effekten af ECB's opkøbsprogram for udvalgte lande i euroområdet og udvalgte nabolande. Effekten af programmet undersøges ved en hændelsesanalyse og ved at estimere en strukturel VAR-model, hvor en kort skyggerente benyttes som mål for den pengepolitiske stilling. Vi finder, at opkøbsprogrammet har bidraget til at reducere de lange renter i euroområdet og i de omkringliggende lande. Som følge af fastkursregimet følger renterne på danske statsobligationer renterne i Tyskland tæt. Lande med en flydende valutakurs har oplevet en styrkelse af valutakursen som reaktion på opkøbene. Den danske krone har været uændret som følge af Nationalbankens interventioner i valutamarkedet. En kontrafaktisk analyse viser, at ECB's opkøbsprogram i begyndelsen af 2015 reducerede løbetidspræmien på danske obligationer med mindst 50 basispoint.
Keywords: E43; E44; E52; F31; F41; 330; Unconventional monetary policy; Quantitative easing; Exchange rate regimes; Shadow short rates; Spillovers; Event study; VAR models